The Meaning of Symbols in The Sedekah Bumi Tradition - Holina Holina; Dwi Wahyuni (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This article provides an explanation of the meaning of symbols in the Sedekah Bumi tradition in the village of Air Putih Ilir, Musi Banyuasin Regency, South Sumatra Province. The research method used in this study is case-study qualitative research. The data were obtained through observation, interview, and documentation techniques, then analyzed by dialogue on Barthes's semiology theory and empirical data obtained at the research location. This article shows that Sedekah Bumi has been carried out continuously from one generation to the next. Sedekah Bumi is also called Sedekah Puyang Tumamia or Puyang Burung Jauh, which is a sacred figure to the villagers of Air Putih Ilir. Sedekah Bumi is a tradition that is carried out after harvesting rice as a form of gratitude to God Almighty. Apart from that, Sedekah Bumi is also meant to ward off disaster and become a medium to strengthen ties between the residents of Air Putih Ilir village. The meaning of symbols in the equipment for the Sedekah Bumi tradition is: first, incense is used because it is thought to speed up the answering of prayers because the spirits of the dead are pleased with the fragrance of incense. Second, heirlooms that are sacred to the residents are sacred objects that have a symbol of struggle from their ancestors. Third, lemang gives a symbol of the life of a society that is so palpable but has a white and sincere heart in it. Fourth, Padi Arang symbolizes the bad nature of humans that must be abandoned.